Analysis of Economic Growth, Agglomeration and Poverty in Southern Sumatera - Retno Agustina Ekaputri; Barika Barika; Azansyah Azansyah; Aan Zulyanto (Universitas Bangka Belitung, 2023)
This study aims to analyze the pattern of economic growth in the provinces of Southern Sumatra. The scope of the study is the provinces of South Sumatra, Bengkulu, Lampung, Riau, Riau Islands, Bangka Belitung Islands and Jambi. Klassen Typology analysis is used to achieve research objectives. Descriptive analysis was also carried out on agglomeration and poverty that occurred in southern Sumatra. The results of the Klassen typology show that 57.14 percent of the provinces in the southern part of Sumatra are included in the Klassen typology as a category of developed but depressed areas (South Sumatra, Bengkulu, Lampung and Jambi). South Sumatra province is the only region that has agglomeration >1. In terms of poverty, Bengkulu is the region with the highest poverty 17.16% in 2020. It is recommended to increase the role of the secondary and tertiary sectors in order to increase the role of industrial agglomeration